Sistema de control interno y su incidencia en la adquisición de bienes y servicios en la gerencia sub regional de Ucayali-Contamana, 2023 - Ramirez Nube, Cesar Eduardo (2024)
The main objective of the final report was to know the incidence of the Internal Control System in the Acquisition of Goods and Services in the Sub Regional Management of Ucayali Contamana, 2023. Carrying out an applied type study of an explanatory level with a non-experimental design, whose The population was 50 administrative workers, to whom a questionnaire was applied to collect information. The results showed that the internal control system is regular (40%); For its part, the acquisition of goods and services is classified as regular (38%). It has been determined that the Internal Control System significantly affects the Acquisition of Goods and Services, being evidenced by a correlation of 51.8% and a value of 0.000; Likewise, the control environment dimension has a coefficient of 0.502 and a significance of 0.000; For their part, the control activities are supported by a coefficient of 0.461 and a sig of 0.000; In addition, monitoring supervision with a coefficient of 0.413 and a sig of 0.000, all of them are significantly related to the acquisition of goods and services where the Pearson statistic was used.